Dynamic Packet Beaconing for GPSR Mobile Adhoc Position Based Routing Protocol Using Fuzzy Logic - Uddin, M.; Alsaqour, Raed; Abdelhaq, Maha; Saeed, Rashid; Alsukour, Ola; Al-Hubaishi, Mohammed; Alahdal, Tariq (Elsevier, 2015)
Greedy perimeter stateless routing (GPSR) is a well-known position-based routing protocol in mobile ad hoc network (MANET). In GPSR, nodes use periodic beaconing (PB) strategy in broadcasting beacon packets to maintain up-to date information on the geographical position of their neighbor nodes within their transmission boundary range. The nodes that receive beacon packets save all known neighbor nodes, along with their geographical position information, in their neighbor list to make effective routing decisions. Most recent studies on position-based routing protocols assume that the position information in the neighbor list of a node is accurate, although only a rough estimate of such position information is actually available to the node. Node mobility causes frequent network topology changes in MANETs. Thus, neighbor-to-neighbor relationships change frequently. Using the PB strategy leads to inaccurate node position information in the neighbor list of a node. In addition, it may cause the routing protocol to make suboptimal decisions and not route packets through the best located neighbor within the transmission range of the node. This study presents an analysis of the influence of position information inaccuracy caused by network parameters such as beacon packet interval time (BPIT) and node moving speed (NMS) on the performance of GPSR position-based routing protocols. To overcome the effect of position information inaccuracy in the neighbor list of a node, we proposed a fuzzy logic dynamic beaconing (FLDB) strategy to improve the reliability of the neighbor list of a node by optimizing time between transmissions of beacon packets in position-based routing protocols. Optimization is based on the correlation between NMS, number of neighboring nodes (NoNNs) and BPIT using fuzzy logic control (FLC) mechanism. The simulation experiment shows the effectiveness of the FLC mechanism in improving overall performance of GPSR position-based routing protocol in terms of beacon packet control overhead, end-to-end delay, non-optimal hop, and false node position.